Behavior Change Communication: Family and Community Approaches - Tri Hastuti Nur Rochimah; Hajar Nur S; Rosyidah Rosyidah (Komunikator, 2021)
Breast and cervical cancers are two deathliest cancers causing women’s death in Indonesia. ‘Aisyiyah developed a model to support, educate and assist women to fight against breast and cervical cancers through behavior change communication in 15 districts. This model is implemented by integrating behavior change communication through family and community support approaches. Research on behavior change communication so far has focused more on the individual level and not many have paid attention to family (husband and wife relations) and community (cultural) factors to encourage individual behavior change. This study aims to explore ‘Aisyiyah’s strategies in behavior change communication (promoting, counselling, and assisting) women through family and community support approaches. This research used a descriptive qualitative method with a case study approach. Data collection are in-depth interview dan documentation. Research locations in five districts; Bantaeng, Mempawah, Sambas, Magelang, and Lamongan. This study revealed that behavior change communication integrated of promotion, family and community approaches was more effective in encouraging women to detect cancer early.